MODERN MODELS OF IMPROVING EDUCATIONAL QUALITY THROUGH DIGITAL DIDACTIC MATERIALS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The rapid transformation of the educational landscape necessitates the integration of advanced digital didactic tools to enhance the quality and efficiency of learning outcomes. This research explores contemporary models of educational delivery centered on interactive digital materials, multimedia resources, and adaptive learning platforms. By analyzing the pedagogical frameworks that support digital integration, the study identifies key mechanisms through which technological assets stimulate cognitive engagement and personalized knowledge acquisition. Particular attention is given to the transition from traditional teaching methodologies to technology-driven environments, emphasizing the role of digital didactics in fostering critical thinking and autonomous learning. The findings suggest that a systematic implementation of structured digital content significantly improves the accessibility and retention of educational information in modern classrooms.